When the guardian locks the gate - Dickie, Marianne; Robinson, Emma (Journal of University Teaching and Learning Practice, 2021)
There are many examples of the regulatory guardian standing at the entry gate of professional life. None have infiltrated so expansively into the education and entry of a profession as the Office of the Migration Agent Registration Authority (OMARA). Since 2006 the OMARA has dictated the course content requirements for the prescribed qualification of migration agents, determined and regulated the exams to be taken by students within each university, and consistently imposed a competency-based education framework that stifles the education and preparation agents need for practice.Australian migration agents fall into a unique space within legal work. They are not lawyers, nor are they clerks; instead, section 276 of the Migration Act 1958 (Cth) gives them the authority to provide immigration assistance to prospective migrants, migrants moving to permanency and citizenship, migrants who have compliance concerns, and asylum seekers, refugees, and those with no legal status. The Migration Act draws a line between migration agents’ work and that of lawyers who provide legal assistance regarding immigration. Both lawyers and graduates with the prescribed qualification can register as migration agents.In 2017 the prescribed qualification for migration agents was changed to a Graduate Diploma to be undertaken at specific universities that had been awarded a government tender to provide the course. In addition, the OMARA designated a stand-alone pre-registration exam to be taken by graduates within a year of the completion of their Graduate Certificate. This exam is currently delivered by one university that is prevented by the OMARA from discussing the course work or exam with the university providers.The exam has been held three times since the change to the qualification was made in 2017. One hundred and thirty-one graduates have sat the exam during that time, and 13 have passed. The extraordinary fail rate of 87% has called into question both the exam and the efficacy of the universities’ teaching. Graduates have considered taking class actions against the provider of the exam, and universities have sought government intervention to assist their students. This article examines the role the OMARA, as the regulator, has played in the education and regulation of migration agents and considers the impact politicisation has had on the development of the education regime.